Discrete-Time Linear Systems Theory and Design with Applications - Gu, Guoxiang; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2012)
Discrete-Time Linear Systems: Theory and Design with Applications combines system theory and design in order to show the importance of system theory and its role in system design. The book focuses on system theory (including optimal state feedback and optimal state estimation) and system design (with applications to feedback control systems and wireless transceivers, plus system identification and channel estimation). This book also: Covers both theory and design for linear systems Discusses wireless transceiver design Addresses the common mathematical features in identification problems arising from the MIMO system identification and MIMO channel estimation Discrete-Time Linear Systems: Theory and Design with Applications is an ideal book for graduate students and practicing engineers from the control area who want to pursue their study in wireless communications and those from the communication and signal processing area who want to learn optimal estimation theory in order to solve complex research problems.
Introduction -- Signals and Systems -- Linear System Theory -- Model Reduction -- Optimal Estimation and Control -- Design of Feedback Control Systems -- Design of Wireless Transceivers -- System Identification -- Appendix A: Linear Algebra -- Appendix B: Random Variables and Processes -- Appendix C: Transfer Function Matrices.
Keywords: Engineering; Mathematical optimization; Systems engineering; Engineering; Calculus of Variations and Optimal Control; Optimization; Circuits and Systems